Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 9 - Roots and Radicals - Chapters 1-9 Cumulative Review Problem Set - Page 433: 77



Work Step by Step

We will factor this trinomial by breaking up the middle term of the trinomial. This is in accordance with the rules of factoring trinomials. $x^{2}+4x-12=0$ $x^{2}-2x+6x-12=0$ $x(x-2)+6(x-2)=0$ $(x-2)(x+6)=0$ $(x-2)=0$ and $(x+6)=0$ $x=2$ and $x=-6$ Therefore, the solution set is {$-6,2$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.